Flexible femtosecond inscription of fiber Bragg gratings by an optimized deformable mirror - Goebel, Thorsten A.; Voigtlaender, Christian; Kraemer, Ria G.; Richter, Daniel; Heck, Maximilian; Siems, Malte P.; Matzdorf, Christian; Reinlein, Claudia; Appelfelder, Michael; Schreiber, Thomas; Thomas, Jens U.; Tuennermann, Andreas; et al. (Optics Letters, 2017)
The period of fiber Bragg gratings is adapted by shaping the wavefronts of ultrashort laser pulses applied in a phase mask inscription technique. A specially designed deformable mirror, based on a dielectric substrate to withstand high peak powers, is utilized to deform the wavefront. A shift of about 11 nm is demonstrated for a Bragg wavelength around 1550 nm.
CRIS-Team Scopus Importer:2023-04-20